Fairness in Contract Extension for Fixed-Term Employment: A Maqashid Syariah Perspective within Indonesia's Labor Law Framework - Arpangi Arpangi; Andhika Yuli Rimbawan; Ratih Mega Puspa Sari; Sivani Ardi Apritania; Heri Oktavianto (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
Indonesia's Employment Law has often been viewed as a legal product that leans toward a capitalist framework, and thus is seen as failing to provide adequate protection for workers under fixed-term employment agreements (PKWT). From an Islamic perspective, Maqashid Shariah offers an alternative approach emphasising justice, welfare, and the safety of fundamental human rights in labour relations. These values stand in contrast to the capitalist system, which tends to prioritise efficiency and economic gain. This study aims to analyse the injustices present in the practice of contract extensions for fixed-term workers under Indonesian labour law, and to explore the relevance of Maqashid Shariah principles as a normative foundation for more just and sustainable labour policies. Employing a normative legal research method, this study examines statutory regulations, legal doctrines, and Islamic legal values. The findings reveal that the absence of a maximum limit on contract extensions under the current labour law creates opportunities to exploit contract workers. These workers may be subjected to repeated contract renewals without being granted permanent status or access to social security benefits. Such uncertainty directly affects family economic stability, and in extreme cases, may drive individuals to seek income through non-halal means. The concept of Maqashid Shariah stresses that economic sustainability, human dignity, and social justice are core objectives of Islamic Law. The academic contribution of this research lies in its proposal of an ethical-normative framework based on Maqashid Shariah to critically assess and reform national labour policies, particularly in enhancing the legal protection of contract workers within a more equitable and welfare-oriented legal system